Electrophysiological study of diaphragmatic myoclonus. Issue 4 (April 1995) - Chen, R; Remtulla, H; Bolton, C F
Abstract : This is the first reported detailed electrophysiological study of diaphragmatic myoclonus. An 86 year old woman had rapid, intermittent epigastric pulsations. Neurological examination and imaging studies of the brain and spinal cord were normal. Needle EMG showed rhythmic contractions of the diaphragm and external intercostal muscles at 4 to 5 Hz. These contractions were often associated with suppression of normal breathing and were capable of maintaining adequate ventilation. Both diaphragms were involved but showed considerable variability in their relative latencies. Automated interference pattern analysis suggested a change in recruitment order, with selective activation of large phrenic motoneurons. The supraspinal mechanisms mediating diaphragmatic myoclonus are different from that of voluntary and involuntary rhythmic breathing, and seem to be unrelated to palatal myoclonus. The generator source is likely related to respiratory centres in the rostral medulla.